The Application of Bibliotherapy on Adolescent Girls with Body Image Dissatisfaction - Hidayat, Widyawati; Sukamto, Monique Elizabeth; Tondok, Marselius Sampe (ANIMA Indonesian Psychological Journal, 2011)
Body image dissatisfaction, caused by a discrepancy between cultural-based ideal body and individual actual body, is experienced by most of adolescent girls. The purpose of this study is to evaluate the effectiveness of bibliotherapy on adolescent girls with body image dissatisfaction. Subjects were 15 senior high school girls, aged 14-17 years, with BMI (Body Mass Index) thin to normal, with average to high body image dissatisfaction. By using pretest-posttest control group design, the subjects were assigned into three groups, i.e. interactive and reading bibliotherapy as experimental groups and the waiting-list control group. One-way analysis of variance (ANOVA) is employed to measure the differences of body dissatisfaction among the three groups. The result showed that there were no significant differences of body dissatisfaction in the pretest – posttest and posttest – follow-up, between the three groups. It means that neither interactive nor reading bibliotherapy was effective in reducing the adolescent girls’ body image dissatisfaction. Ketakpuasan bayangan diri yang disebabkan oleh ketaksesuaian antara bentuk tubuh ideal berdasarkan budaya dan bentuk sebenarnya tubuh individual, dialami oleh kebanyakan gadis remaja. Tujuan penelitian ini adalah menilai efektivitas terapi bacaan terhadap remaja putri yang menyandang ketakpuasan bayangan diri. Para subjek adalah 15 siswa SMA, berusia antara 14-17 tahun, dengan indeks massa tubuh (body mass index = BMI) kurus hingga normal, dengan ketakpuasan rata-rata hingga tinggi. Dengan desain prauji-pascauji dan kelompok kendali, para subjek dibagi menjadi tiga kelompok: kelompok bacaan pustaka interaktif dan kelompok bacaan pustaka sebagai kelompok percobaan, dan kelompok daftar tunggu sebagai kelompok kontrol. Dipakai analisis varian satu arah (ANOVA) untuk mengukur perbedaan bermakna ketakpuasan bayangan diri di antara ketiga kelompok. Hasil-hasil menunjukkan bahwa tak ada perbedaan bermakna baik pada kelompok prauji–pascauji dan pascauji–follow up, menunjukkan bahwa terapi bacaan interaktif maupun bacaan pustaka tak efektif dalam menurunkan rasa ketakpuasan para gadis remaja.